2020
DOI: 10.1021/acsphotonics.0c00611
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Circular Dichroism Spectroscopy on Periodic Dual Nanostructures

Abstract: Increasing the sensitivity of chiral spectroscopic techniques such as circular dichroism (CD) spectroscopy is a current aspiration in the research field of nanophotonics. Enhancing CD spectroscopy depends on two complementary requirements: the enhancement of the electromagnetic fields perceived by the molecules under study and the conservation of the helicity of those fields, guaranteed by duality symmetry. In this work, we introduce a systematic method to design nanostructured dual periodic photonic systems c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 57 publications
0
42
0
Order By: Relevance
“…On the other hand, for cylindrically symmetric particles, the absence of backscattered light follows from the preservation of EM helicity [14][15][16][17][18]. Conservation of helicity has proven crucial in many applications such as enhanced chiral light-matter interactions [19][20][21][22][23][24][25], or in the spin-orbit interactions of light [26][27][28][29][30][31][32]. In this vein, it has been reported that from a relatively simple far-field measurement of the EM helicity at a right angle, the radiation pattern of the dipolar particle is inferable [33].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, for cylindrically symmetric particles, the absence of backscattered light follows from the preservation of EM helicity [14][15][16][17][18]. Conservation of helicity has proven crucial in many applications such as enhanced chiral light-matter interactions [19][20][21][22][23][24][25], or in the spin-orbit interactions of light [26][27][28][29][30][31][32]. In this vein, it has been reported that from a relatively simple far-field measurement of the EM helicity at a right angle, the radiation pattern of the dipolar particle is inferable [33].…”
mentioning
confidence: 99%
“…In a spin-orbit framework, this phenomenon precludes the full angular momentum exchange from spin to orbit after scattering, inhibiting the emergence of an optical vortex in the backscattering direction. Moreover, recently, massive efforts have been dedicated to maximizing the sensitivity of circular dichroism (CD) spectroscopy of chiral molecules [19][20][21][22][23][24][25]. Some of these theoretical developments have relied on meeting Kerker's first condition in high index nanoparticles to preserve the helicity of the scattered electromagnetic fields.…”
mentioning
confidence: 99%
“…4(f), integrating the total contribution of entire SS yields no net energy transport along the bias field, as expected due to equilibrium conditions (see SI section B.2). Interestingly, analyzing the polarization state of each edge channel, we observe a well defined sign of the spatially-averaged opti-cal chiralityc > 0 [42][43][44][45][46][47] through the entire SS (see SI section B.3).…”
Section: Chiral Surface Statesmentioning
confidence: 97%
“…The inter-particle distance is here chosen to coincide with the Kerker condition (l = 1208 nm), to combine the benefits of field enhancement and helicity preservation. 31 The elongated GoldHelix structure already illustrated that as a cluster structure extends in an anisotropic way, along at least one direction, the collective optical response becomes more dependent on the incidence direction. This can be understood from the perspective of a multipolar expansion, as used in the superposition T-matrix framework.…”
Section: View Article Onlinementioning
confidence: 99%